O Mosteiro das Beneditinas da Purificação : obra de Fernando Mergulhão, monumento emblemático de Moimenta da Beira - Dias, Geraldo J. A. Coelho (História: revista da Faculdade de Letras da Universidade do Porto, 2018)
The occurrence of the 400year anniversary of Fernando Mergulhão’s death (14th November 1604-2004), abbot of S. Clemente de Basto, judge of the High Court of Archbishop D. Frei Bartolomeu dos Mártires, and founder of Moimenta da Beira Monastery provided the author with subject matter to dwell on the Mergulhão family and the Benedictine monastery. In truth, Fernando Mergulhão belonged to a family of Spanish origin, followed an ecclesiastical career, as well as his brother, who became a Jesuit. Of his four sisters, only one married, and the others entered the Semide Monastery, in Coimbra, as Benedictine nuns. It was certainly for them, and for remedy of his soul and his parents’, that he decided to found with his patrimony the Monastery of Our Lady of the Purification in his native land. The author traces the history of the monastery, founded in 1596 and closed around 1812, at which time its nuns were integrated in the Convent of Chagas, Lamego.